SISTEM TOP UP SALDO DAN PEMBAYARAN MENGGUNKAN RFID - Sepina, Sepina; Kartika Magdalena; Dwisaputra, Indra; Ocsirendi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Radio Frequency Identification (RFID) technology has emerged as an innovative solution to improve payment systems and balance top ups. The system uses radio waves to conduct contactless transactions, allowing users to top up balances and make payments quickly and easily by simply bringing the RFID card or tag closer to a prepared reader. This research aims to evaluate the implementation of RFID technology in the payment system, assess its security, and analyze its effectiveness in reducing transaction time and operational costs. The methodology used includes data collection from case studies on several platforms that have implemented RFID technology for payments and balance top-ups. The analysis also included a survey of users to assess their satisfaction and response to the new system. The results showed that the use of RFID does offer faster transactions and a significant reduction in operational costs. In addition, security features developed as part of RFID technology, such as encryption and two-factor authentication, have been effective in reducing the risk of fraud and identity theft.